2009
DOI: 10.1016/j.proche.2009.07.300
|View full text |Cite
|
Sign up to set email alerts
|

Improved Energy Harvesting from Wideband Vibrations by Nonlinear Piezoelectric Converters

Abstract: Vibration harvesters typically are linear mass-spring devices working at resonance. A different approach is here proposed based on nonlinear converters that exploit stochastic resonance with white-noise excitation. A piezoelectric beam converter is coupled to permanent magnets creating a bistable system bouncing between two stable states in response to random excitation. Under proper conditions, this significantly improves energy harvesting from wide-spectrum vibrations. A cantilever beam with added nonlineari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 8 publications
2
95
0
Order By: Relevance
“…Ferrari et al [11] have developed a bistable configuration of the cantilever-based design shown in Fig. 1.…”
Section: Bistable Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrari et al [11] have developed a bistable configuration of the cantilever-based design shown in Fig. 1.…”
Section: Bistable Configurationmentioning
confidence: 99%
“…Alternatively, in some applications a harvester that exhibits non-linear behaviour (e.g. bistability [11]) may deliver the most energy.…”
Section: Introductionmentioning
confidence: 99%
“…This system has been studied extensively in the context of energy harvesting especially for the case of white noise excitation (Daqaq, 2011;Daqaq, 2012;Gammaitoni et al, 2009;Ferrari et al, 2010). However, for realistic setups it is important to be able to optimize/predict its statistical properties under general (colored) excitation.…”
Section: Methods Descriptionmentioning
confidence: 99%
“…The resonance peak of vibrating beams fixed at one end can be broadened by mounting magnets at their free end and placing a fixed repelling magnet opposite to it [6,7] (cf. Figure 6).…”
Section: Piezoelectric Beammentioning
confidence: 99%